PENGARUH FIRM SIZE DAN GROWTH PADA MANAJEMEN LABA - Laras Pangesti (Faculty of Economics and Business, Universitas Malikussaleh, 2019)
This study aims to determine the effect of Firm Size and Growth on earnings management in manufacturing companies listed on the IDX. Quantitative research using 30 respondents and purposive sampling methods, namely (1) Manufacturing Companies that have been listed on the Indonesia Stock Exchange that have submitted audited financial statements and notes to the financial statements as of December 31, according to the research period. (2) Companies that submit complete data in accordance with the information needed, namely Firm Size, Growth and Profit Management. And using secondary data is the financial statements of manufacturing companies that meet the purposive sampling requirements that are analyzed using multiple linear regression with SPSS version 22. The results of this study indicate (1) Firm Size has a significant negative effect on earnings management, (2) Growth has no effect on profit management. Benefits of research, (1) For practitioners, input for investors in investing in the capital market is also a reference to make a healthy company with this research. (2) For Theoretical, Add insight into Firm Size, Growth and Earnings Management.